Craniometrical differentiation of gray brocket deer species from Brazil - González, Susana; Bonfim Mantellatto, Aline Meira [UNESP]; Barbanti Duarte, José Maurício [UNESP] (Museo Argentino de Ciencia Naturales, 2018)
The genus Mazama (brocket deer) constitutes successful adaptive radiation, with a wide distribution in the Neotropical region. However, the taxonomy and systematics of its species and subspecies is still controversial. The objective of this contribution was to carry out a comparative craniometric study of specimens deposited in Brazilian museums of M. gouazoubira (Mg) and M. nemorivaga (Mn), in order to characterize these cryptic species. We performed 36 measures on 87 skulls of adult specimens (Mg = 32 females and 27 males; Mn = 14 females and 14 males). The sample was compared by analysis of variance and multivariate analysis of principal components and discriminant. In most cranial measurements, males and females of M. gouazoubira were 5% larger, with the exception of 3 measures: premolar-prosthion, basifacial axis, and least breadth between the orbits, that were larger in males and females of M. nemorivaga. This study showed significant differences between the two taxa that would validate the distinction of both species. To examine in more detail the dynamics of the variation of these two taxa it is necessary to increase the sample size in order to analyse them in a geographical and genetic context.
Keywords: Craneometrical; Gray brocket deer; Mazama gouazoubira; Mazama nemorivaga